2(3z-1)-2(3-2z)=4

Simple and best practice solution for 2(3z-1)-2(3-2z)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3z-1)-2(3-2z)=4 equation:


Simplifying
2(3z + -1) + -2(3 + -2z) = 4

Reorder the terms:
2(-1 + 3z) + -2(3 + -2z) = 4
(-1 * 2 + 3z * 2) + -2(3 + -2z) = 4
(-2 + 6z) + -2(3 + -2z) = 4
-2 + 6z + (3 * -2 + -2z * -2) = 4
-2 + 6z + (-6 + 4z) = 4

Reorder the terms:
-2 + -6 + 6z + 4z = 4

Combine like terms: -2 + -6 = -8
-8 + 6z + 4z = 4

Combine like terms: 6z + 4z = 10z
-8 + 10z = 4

Solving
-8 + 10z = 4

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 10z = 4 + 8

Combine like terms: -8 + 8 = 0
0 + 10z = 4 + 8
10z = 4 + 8

Combine like terms: 4 + 8 = 12
10z = 12

Divide each side by '10'.
z = 1.2

Simplifying
z = 1.2

See similar equations:

| -58-9x+3x=74 | | 5x-15=15-x | | 5x-15=15-z | | -6(t+4)=12 | | 15x+10=10x | | x^2-8x=7 | | 6m-3-2m=7m-4-1m | | 3-3x=17+4x | | x+8=x-7 | | x*2+6X=7 | | 4x+24=7x | | a=4+-1b | | 2a=4a | | 2(4+-1b)+3b=11 | | 2(4+-1b)+3b=4 | | -7x+y=-19 | | 0.50x+0.45(50)=34.5 | | 3(-1.5b)-b=11 | | -2r+5.1=8.5 | | (-2x+5)(x-4)=0 | | -6(4x-1)+2=-24x+8 | | 4n+2.8=9.2 | | 2.8-2t=-3.2 | | 3m-2=m+8 | | x+.666=.1666 | | 8-2x-6-8x=4 | | 1.1=4y+13.9 | | 3a-b=11 | | 16.85=3.95+3c | | 5-3(x+4)=6 | | 4f+2=8 | | 8+(7x-6)=3 |

Equations solver categories